Diseño estructural para seguidor solar de un eje en una estación fotovoltaica de 1 kw - Caisatoa Condor, Cristian Danilo (2022)
This project is focused on the structural design and construction of a single-axis solar tracker which will provide a better collection of solar radiation to the photovoltaic panels for the estimated power generation of 1kW, which is implemented on the terrace of Block B of the Technical University of Cotopaxi, as initial data were considered some aspects such as: the geographical location of the project, size and weight of the solar panels, whose information was used to select the type of structure to be designed. The structural analysis consists of physical calculations that contributed to the selection and sizing of the materials with which the structure was built, which is made of galvanized square tube 4in x 0.12in thick for its four main supports, which are the main responsible for supporting the weight of the shaft and the solar panels as well as the fasteners of the same, For the shaft was used galvanized pipe 2in diameter by 0.12in thick which was selected by catalog for its rigidity and load capacity, for the movement of the shaft was implemented bearings which are placed at the top of the main supports, the structure is designed to accommodate 8 solar panels in a row which can be of different dimensions not greater than 1. 65 m high and 0.99 m wide, since the type of structure is coupling type; through simulation it was obtained that the maximum safety coefficient of the structure is 15, which indicates that the structure is oversized, thus supporting a greater load capacity.